Zum Problem der Bürgerbestimmung in der aristotelischen Politik - Jinek, Jakub (ΠΗΓΗ/FONS, 2016)
The paper disproves the widely held interpretation of Aristotle’s statement that the concept of the citizen varies with the constitution. I claim that it gives no evidence for any positivism or constitutional relativism. What Aristotle truly intends here is to put emphasis on his idea of the good life in a city that consists of a variety of Jakub Jinek Π Η Γ Η / F O N S I (2016), 123-144 124 forms and ways. This variety is generally desirable and thus prescriptive. It is only under these conditions that the constitution is „the Form of the city“ which determines the citizenship. The concept of the citizen is thus conceived as rather broad and the argument reveals to be a plea for the rule of majority (polity). But on the other hand, the definition of citizen enables to distinguish the virtue of the good man from that of the good citizen und thus to differentiate among the good constitutions.
Keywords: Citizenship; Constitution; Polity; Aristotelian Politics